2023
DOI: 10.26434/chemrxiv-2023-l5j08
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced Hydrogen Bonding via Epoxide-functionalization Restricts Mobility in Poly(ethylenimine) for CO2 Capture

Sichi Li,
Marcos F. C. Andrade,
Anthony J. Varni
et al.

Abstract: Epoxide-functionalization has emerged as an effective strategy for enhancing the oxidative stability of poly(ethylenimine)-based CO2 capture sorbents. However, the underlying mechanism remains largely unexplored. Here we combine first-principles modeling, material synthesis, and characterizations to investigate the impact of epoxide-functionalization on hydrogen bonding and mobility in poly(ethylenimine) (PEI). Blue-moon ensemble and deep potential molecular dynamics simulations reveal that epoxide-functionali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Ratiometric analysis was used to assess additional physical phenomena in that work, including polymer hysteresis. In a second study, Li et al demonstrated that a similar ratiometric analysis of THPE emission could serve as a measure of the relative mobility of several different epoxide-functionalized aminopolymers with different degrees of hydrogen bonding . Fluorescence data was correlated with NMR relaxometry data to provide more quantitative analysis of polymer mobility.…”
Section: Resultsmentioning
confidence: 99%
“…Ratiometric analysis was used to assess additional physical phenomena in that work, including polymer hysteresis. In a second study, Li et al demonstrated that a similar ratiometric analysis of THPE emission could serve as a measure of the relative mobility of several different epoxide-functionalized aminopolymers with different degrees of hydrogen bonding . Fluorescence data was correlated with NMR relaxometry data to provide more quantitative analysis of polymer mobility.…”
Section: Resultsmentioning
confidence: 99%